Deep Reinforcement Learning with a Combinatorial Action Space for Predicting Popular Reddit Threads - He, Ji; Ostendorf, Mari; He, Xiaodong; Chen, Jianshu; Gao, Jianfeng; Li, Lihong; Deng, Li (EMNLP 2016, 2016)
We introduce an online popularity prediction and tracking task as a benchmark task for reinforcement learning with a combinatorial, natural language action space. A specified number of discussion threads predicted to be popular are recommended, chosen from a fixed window of recent comments to track. Novel deep reinforcement learning architectures are studied for effective modeling of the value function associated with actions comprised of interdependent sub-actions. The proposed model, which represents dependence between sub-actions through a bi-directional LSTM, gives the best performance across different experimental configurations and domains, and it also generalizes well with varying numbers of recommendation requests.